How the Quality of Institutions Affects Technological Deepening in Developing Countries - Clarke, George R.G. (World Bank, Washington, DC, 2014)
This paper assesses the effect of institutional quality on research and development (R&D) expenditures in developing countries. The paper finds that the risk of expropriation and the rule of law are correlated with R&D expenditures. Since both institutional variables increase as institutional quality improves (i.e., as risk of expropriation decreases and rule of law improves), this suggests that stronger institutions encourage greater R&D expenditures. The result for the risk of expropriation is more highly significant and far more robust than the result for the 'rule of law'. Although R&D is not the primary way that developing countries gain access to technology, this result is interesting for at least two reasons. First, R&D might encourage technological deepening better than other methods that developing countries use to gain access to technology (e.g., through foreign direct investment (FDI) or capital goods imports). Second, past work has shown that another important way that developing countries gain access to technology, through FDI, is also positively correlated with institutional quality (i.e., as institutional quality improves, FDI increases).